ISSUES OF UZBEK AND COMPARATIVE FOLKLORE STUDIES - Kalandarova Dilafruz Abdujamilovna (Journals Park Publishing, 2025)
This article examines the issues of Uzbek folk oral literature and comparative folklore, its place in folklore, the role of epic genres, including the epic genre, in a deeper, broader and more complete study, allowing us to identify similarities and differences in the plot and motifs, heroes, their adventures, experiences, and the development of events in general. It is once again emphasized that the common and differential features of the work, the issues of time and space in them, the interaction of one epic with another, and the debates on existing views on folklore contribute to the development of comparative studies, which contribute to the further development of the field.
Keywords: Folklore, comparative folklore, translation, research, comparison, epic, variant, version, plot, motif, overall effect.